FACTORS ANALYSIS REGARDING THE GROSS PROFITABILITY OF WINE MARKET - CASE STUDY - Niţescu, Cristina (Economics of Agriculture, 2012)
Small vineyard holdings become profitable in a market increasingly globalized. However through a process of structural adjustment supported by external and internal funds, technical modernization is essential in conditions of appropriate training structures, so that it can be used to the full resources available. This provides the vine and wine products a high quality with minimum costs, tailored for the use of modern technologies, with a high labour productivity resulted in a positive economic environment as well as a stable economy which in the end will provide support for a profitable export through efficient sales just like the most vine productive countries.